Pa Deang Inscriptions: the Religious Perspective - Wongsathit, U-tain (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 12 No 1 (2020): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The Buddhism in Sukhothai period (1238 – 1438 A.D.) is regularly presented in very positive manner as the ideal in Buddhist way. Three inscriptions from Wat Pa Daeng, however, shows the reality of conflict in Buddhism at the time. This conflict leads to the sue in the royal court. This article aims to scrutinize these three inscriptions from Wat Pa Daeng, dated 1406 A.D., to show the customs of Buddhism in Sukhothai period from the reign of Dhammaraja I to Dhammaraja III. The study focuses the arrival of Arannavasi or forest monastery sect from Sri Lanka through Mon state. The venerable Sumana had played very significant role in spreading the Arannavasi practice with the immense support from king Dhammaraja I. The Pa Daeng inscriptions also reveal practice of the convertion, the promotion of chief abbot, the sue to royal court and the way to resolve the case by the king and Sangha. This indicates the seperation of law between Sangha and state. These informations are very usful for the study of history of Buddhism in Thailand as well.